Tax Policy of the Republic of Bulgaria for the Period 2007-2013 - Pavlova, M. (Економічний вісник Донбасу, 2014)
The fiscal policy, conducted by the state, in its two dimensions - government revenues and their targeted allocation in accordance with the socio-economic needs (government expenditures) - is the basis of the national economy development. The accumulation of sufficient state’s revenues in order to ensure its expenditures is a task of primary importance, especially in terms of macroeconomic instability, when the government intervention is essential for the timely overcoming of the economic recession or crisis. In this regard, the analysis of the revenue side of the consolidated fiscal program and the evaluation of ongoing state policy of the Republic of Bulgaria in times of economic crisis are current topics with scientific and applied interest. In the study, the importance of the separate tax forms for the state treasury is revealed, tendencies and tax forms’ development through structural and dynamic analysis of the revenue part of the consolidated fiscal program are outlined and the state tax policy for the period 2007-2013 is estimated. Бюджетна політика, що проводиться державою, має два виміри - урядові доходи і їх цілеспрямоване розміщення відповідно до соціально-економічної необхідності (урядові витрати) - лежить в основі розвитку народного господарства. Накопичення доходів достатніх державі для того, щоб гарантувати її витрати - завдання першорядної ваги, особливо в термінах макроекономічної нестійкості, коли урядове втручання істотне для своєчасного подолання економічного спаду або кризи. В цьому відношенні, аналіз митної сторони консолідованої фінансової програми і оцінки тривалої державної політики Республіки Болгарія за час економічної кризи - поточні теми з науковим і прикладним інтересом. Бюджетная политика, проводимая государством, в нем два измерения - правительственные доходы и их целенаправленное размещение в соответствии с социально-экономической необходимостью (правительственные расходы) - лежит в основе развития народного хозяйства. Накопление доходов достаточных государству для того, чтобы гарантировать его расходы - задача первостепеннойважности, особенно в терминах макроэкономической неустойчивости, когда правительственное вмешательство существенно для своевременного преодоления экономического спада или кризиса. В этом отношении, анализ таможенной стороны консолидированной финансовой программы и оценки продолжающейся государственной политики Республики Болгария за время экономического кризиса - текущие темы с научным и прикладным интересом.